Chapter I prelievi non fondiari - GINATEMPO, MARIA AUSILIATRICE (Reti Medievali E-Book, 2023)
The essay attempts a survey of the economic and social impact of non-landed levies, meaning by this all the drainages of wealth in which the exercise of coercive powers played a decisive role. It follows a "macro" and "geo" economic approach, paying particular attention to the redistribution of wealth on the territory. After an inventory of the different types of levies, it proposes an overview for 4 macro-areas (1. the Alpine and Apennine areas; 2. the marginal areas; 3 the expanding areas of the South and Sicily: 4. Po Valley), with a focus on levies that appear to have the greatest impact. That is: tolls and other charges on trade; control of collective resources; personal burdens (military and civil); and also state taxes, monopolies or tributes belonging to the state and granted to the lords in various forms of delegation, not ubiquitous, but sometimes important. Only a few hints are dedicated to judicial proceeds, rights on the circulation of land and people, and tributes on the borderline with the landed-based ones.